Kelayakan Usaha Penangkapan Ikan Menggunakan Alat Tangkap Bubu Dasar di Pangkalan Pendaratan Ikan (PPI) Kurau Kabupaten Bangka Tengah - Maryani Maryani; Sudirman Adibrata; Teguh Ferdinand (Journal of Tropical Marine Science, 2021)
Basic bubu fishing equipment is one of the fishing equipment in the Fish Landing Base (PPI) Kurau Central Bangka Regency. Fishing business with basic bubu fishing equipment is a potential business with a catch of high economic value in the form of demersal fish. The purpose of this study is to analyze the feasibility of fishing business by using basic bubu fishing equipment at the Kurau Fish Landing Base (PPI) In Central Bangka Regency. Data collection methods used in this research are survey, interview and kuesinoner methods. Data analysis used is descriptive quantitative analysis. The result of business feasibility analysis from the basic bubu business is the required investment cost value of Rp. 84.050.000,00, with a total cost of Rp. 196,372,661.00/year. Analysis of business criteria is known the value of receipts of Rp. 233,775,000.00/year, income of Rp. 37,402,339/year and PP of 2.25 years. Analisis kiteria investasi nilai nilai NPV sebesar Rp. 57.915.583,00, nilai B/C Ratio itu 1.19 dan nilai IRR sebesar 34,33%. Analisis yaitu yaitu nilai NPV positif, B/C Ratio > 1 dan IRR >discount rate. This shows that the basic bubu business at Kurau central Bangka regency Fish Landing Base (PPI) has a good and feasible opportunity to run.